The Effect of Regional Original Income, Balanced Funds and Capital Expenditures on the Government's Financial Performance in The Regency/City of North Sumatra Province - Siti Khadijah Mtd; Maryam Batubara; Nur Ahmadi Bi Rahmani (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine and analyze the effect of Regional Original Income, Balancing Funds and Capital Expenditures on the Financial Performance of Regency/City Governments in North Sumatra Province. The population of this research is districts/cities in North Sumatra Province as many as 33 districts/cities in the 2017-2021 observation year. The type of sample in this study uses a saturated sample where the entire population is sampled. The data is processed by using panel data regression statistical test with the help of Econometric Views (Eviews) software version 10. The results of this study prove that Regional Original Income, Balancing Funds, and Capital Expenditures simultaneously affect the Financial Performance of Regency/City Governments in North Sumatra Province. Partially Local Original Income, and Capital Expenditures have a significant effect on Financial Performance. while the balancing fund has no effect on financial performance. Regency/City Regional Government in North Sumatra Province